The Co–Au interface in bimetallic nanoparticles: a high resolution STEM study - Mayoral, Alvaro; Mejía Rosales, Sergio; Mariscal, Marcelo M.; Pérez Tijerina, Eduardo Gerardo; Yacamán, Miguel José (Royal Society of Chemistry Publishing, 2010)
We report the formation of Au/Co nanoparticles and their characterization by aberration (Cs) corrected scanning transmission electron microscopy (STEM). The nanoparticles were synthesized by inert gas condensation, forming initially core-shell and bimetallic crystals. However, after thermal treatment at normal atmospheric conditions, the Co nanoparticles changed their morphology into a fine layer forming a perfect interface with the gold. The ordering of the zone rich in Co presents a fcc arrangement matching the gold lattice. The atomic analysis on the interface and the comparison of the STEM images with numerical simulations corroborated the atomic substitution of gold by cobalt.